The Association between Sociodemographic Factors, Lifestyle Score, and Body Mass Index with COVID-19 Infection: A Cross-Sectional Study - Delvarianzadeh, Mehri; Atefi, Masoumeh; Ebrahimi, Mohammad Hossein; Bahar, Aisa; Ghelichi, Faride; Nowrozi, Hadi; Talebi, Seyedeh Solmaz (Shahroud Journal of Medical Sciences, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic is a global health crisis; therefore, the prevention and treatment of this disease is a top priority for health worldwide. COVID-19 infection has been associated with various factors. This study aimed to examine the correlations between COVID-19 infection and various sociodemographic factors, lifestyle score, and obesity. Methods: The present study was a cross-sectional study. Data were collected from students of the Shahroud University of Medical Sciences in 2021. The outcome measures were body mass index (BMI), sociodemographic factors, and lifestyle score, which was evaluated with a validated Walker questionnaire. Logistic regression was employed to investigate the associations between exposure variables and COVID-19 infection. Results: Data from 382 students (43.71% infected with COVID-19) were analyzed. After adjusting for covariates, obese participants were 73% more likely to have COVID-19 infection than participants with normal body weights (OR=1.73; 95% CI: 0.25, 3.22; P-value=0.022). A strong lifestyle score was associated with 8% reduced likelihood of COVID-19 infection compared with a moderate lifestyle score (OR=0.92; 95% CI: 0.86, 0.98; P-value=0.04). Conclusions: Our study revealed that increasing lifestyle score and reducing obesity may be helpful in the prevention of COVID-19 infection. Further research must validate this possible association.